2015
DOI: 10.1089/end.2014.0249
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde Intrarenal Surgery with Combined Spinal-Epidural vs General Anesthesia: A Prospective Randomized Controlled Trial

Abstract: Objective: Retrograde intrarenal surgery (RIRS) involves a minimally invasive stone surgery, lending itself potential to combined spinal-epidural anesthesia (CSEA), although it is performed preferably under general anesthesia (GA). This prospective randomized study was undertaken to evaluate the feasibility and efficacy of CSEA for patients undergoing RIRS. Patients and Methods: Seventy consecutive patients who were scheduled for RIRS were randomized to receive CSEA (n = 35) or GA (n = 35). Operative time, sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 10 publications
(15 reference statements)
1
33
0
2
Order By: Relevance
“…No significant difference was detected among groups in terms of stone clearance (p=0.215). Zeng et al (15) performed f-URS in a total of 65 patients under GA (n=34) and RA (n=31). Similar to our results, their stone clearance rates were 70.6% in GA and 67.7% in RA group, not significantly different.…”
Section: Discussionmentioning
confidence: 99%
“…No significant difference was detected among groups in terms of stone clearance (p=0.215). Zeng et al (15) performed f-URS in a total of 65 patients under GA (n=34) and RA (n=31). Similar to our results, their stone clearance rates were 70.6% in GA and 67.7% in RA group, not significantly different.…”
Section: Discussionmentioning
confidence: 99%
“…With the regional anesthesia techniques like spinal anesthesia, the patient may feel pain, unwanted traumas may occur due to inadequate relaxation of the ureters or uninhibition of variable breathing movements. Zeng et al [17] compared the patients who had undergone combined spinal and epidural anesthesia (CSEA) (31 patients) with general anesthesia (GA) (34 patients). They reported that the results in CSEA group were not worse than GA group and no conversion to GA was required in CSEA group.…”
Section: Anesthesiamentioning
confidence: 99%
“…For this reason the type of anesthesia used can influence the outcome of the procedure. Various types of anesthesia have been used to perform RIRS; these include: general anesthesia (GA), combined spinal-epidural anesthesia (CSEA) 6 and sacral block anesthesia 7 .…”
Section: Retrograde Intrarenal Surgery (Rirs) With the Use Of Holmiummentioning
confidence: 99%
“…However no specific indications on the gold standard have been reported. The 2016 European Association of Urology guidelines on urolithiasis state: "Most interventions are performed under general anesthesia, although local or spinal anesthesia is possible" This is debatable and may be interpreted in different ways by the clinicians who should make the decision on the most appropriate type of anesthesia on individualized basis.Only one prospective randomized trial comparing CSEA to GA has been published so far6 ; it included 70 patients undergoing RIRS. The authors reported no difference in terms of operative and stone fragmentation time, post-operative pain, incidence of complications, stone-free rate and hospital stay between the two groups respectively.…”
mentioning
confidence: 99%